Proposal of an Acceptability Model for Telerehabilitation Platforms: Perspective of Health Professionals and Patient - Silva-Quiroz, J; Galvez-Manriquez, D; Santander-Tapia, P; Delgado-Cadena, L (Springer Nature, 2025)
Telerehabilitation platforms are an innovative tool in the health area to support medical centers in their rehabilitation services. Being a recent and widely used tool, it is still evolving, so it is essential to have an evaluation mechanism that allows diagnosing the behavior and reaction of users to this type of platform. This article proposes an acceptance evaluation model based on the identification of the factors that characterize the user s decision to use this type of platform. Assessing this user intention has implications for healthcare centers as it provides support to enhance the design of their platforms.The proposed model is an aid to decision making to improve the user experience with this type of platform and thus improve the remote service. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.